Faeces as a novel material to estimate lyssavirus prevalence in bat populations. (8th December 2019) - Begeman, Lineke; Kooi, Engbert A.; van Weezep, Erik; van de Bildt, Marco W. G.; Reusken, Chantal B. E. M.; Lina, Peter H. C.; Koopmans, Marion P. G.; van den Brand, Judith M. A.; Kuiken, Thijs
Abstract: Rabies is caused by infection with a lyssavirus. Bat rabies is of concern for both public health and bat conservation. The current method for lyssavirus prevalence studies in bat populations is by oral swabbing, which is invasive for the bats, dangerous for handlers, time‐consuming and expensive. In many situations, such sampling is not feasible, and hence, our understanding of epidemiology of bat rabies is limited. Faeces are usually easy to collect from bat colonies without disturbing the bats and thus could be a practical and feasible material for lyssavirus prevalence studies. To further explore this idea, we performed virological analysis on faecal pellets and oral swabs of seven serotine bats ( Eptesicus serotinus ) that were positive for European bat 1 lyssavirus in the brain. We also performed immunohistochemical and virological analyses on digestive tract samples of these bats to determine potential sources of lyssavirus in the faeces. We found that lyssavirus detection by RT‐qPCR was nearly as sensitive in faecal pellets (6/7 bats positive, 86%) as in oral swabs (7/7 bats positive, 100%). The likely source of lyssavirus in the faeces was virus excreted into the oral cavity from the salivary glands (5/6 bats positive by immunohistochemistry and RT‐qPCR) or tongue (3/4 bats positive by immunohistochemistry) and swallowed with saliva. Virus could not be isolated from any of the seven faecal pellets, suggesting the lyssavirus detected in faeces is not infectious. Lyssavirus detection in the majority of faecal pellets of infected bats shows that this novel material should be further explored for lyssavirus prevalence studies in bats.